The internet of animals human-animal relationships in the digital age - Lupton, Deborah 1963- (polity, 2023)
'The internet is made of cats' is a half-jokingly made claim. Today, animals of all shapes and sizes inhabit our digital spaces, including companion animals, wildlife, feral animals and livestock.In this book, Deborah Lupton explores how digital technologies and datafication are changing our relationships with other animals. Playfully building on the concept of 'The Internet of Things', she discusses the complex feelings that have developed between people and animals through the use of digital devices, from social media to employing animal-like robots as companions and carers. The book brings together a range of perspectives, including those of sociology, cultural geography, environmental humanities, critical animal studies and internet studies, to consider how these new digital technologies are contributing to major changes in human-animal relationships at both the micropolitical and macropolitical levels. As Lupton shows, while digital devices and media have strengthened people's relationships to other creatures, these technologies can also objectify animals as things for human entertainment, therapy or economic exploitation.This original and engaging book will be of interest to scholars and students across the social sciences and humanities
Introduction; 1 Conceptualising Humans, Animals and Human-Animal Relations; 2 Animal Enthusiasts, Activism and Politics in Digital Media; 3 The Quantified Animal and Dataveillance; 4 Animal Cuteness, Therapy and Celebrity Online; 5 Animal Avatars and Zoomorphic Robots; Conclusion: Reimagining Human-Animal Relations; Appendix; References; Index
Keywords: Internet; Neue Medien; Tiere; Mensch; Politik, Gesellschaft, Wirtschaft